Chapter Study in mobility: Tian Dewang and his experience at the University of Florence (1935-1937) - GAO, CHANGXU (Studi e saggi, 2023)
It is commonly known that Italian departments, or at least Italian literature courses, were inaugurated in Chinese universities in the 1980s. Less known is the period of the 1930s, in which a Chinese student who specialized in Foreign Literature at Tsinghua University obtained a scholarship by the Italian government to study in Italy for two years: Tian Dewang 田德望 (1909-2000) was the first Chinese student to study Italian literature in Italy. In the 1980s he became a famous professor and translator of Italian literature, and was the first to complete an entire translation of Dante's The Divine Comedy into Chinese. This paper is aimed at reconstructing the relation between the Chinese student and his Italian professor, Attilio Momigliano, and how the 'mobility experience' of Tian Dewang in Italy inspired and influenced his future academic career.